2016
DOI: 10.1093/gastro/gow030
|View full text |Cite
|
Sign up to set email alerts
|

Budd-Chiari syndrome associated with coeliac disease: case report and literature review

Abstract: We report a case of Budd-Chiari syndrome occurring in a patient with coeliac disease, who presented with symptoms of increased abdominal girth, right upper quadrant pain and shortness of breath for three weeks prior to admission. Initial assessment revealed the presence of moderate ascites, hepatosplenomegaly and right-sided pleural effusion. Further diagnostic work-up established a diagnosis of chronic Budd-Chiari syndrome. Interestingly, complete screening for pro-thrombotic factors was negative. A review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…One multicentric case series showed that the majority of patients reported belonged to the female gender and presented in the third or fourth decade [1]. Likewise, our patient was also a female in her second decade of life.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…One multicentric case series showed that the majority of patients reported belonged to the female gender and presented in the third or fourth decade [1]. Likewise, our patient was also a female in her second decade of life.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, some cases of Budd-Chiari syndrome with chronic celiac disease have been reported from North Africa. Meanwhile, few cases have also been reported from other countries like Spain, Argentina, Turkey India and Czech Republic [1,6,7]. To the best of our knowledge, we present the first reported case of BCS with CD in Pakistan.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Splenic vein thrombosis was reported in one case. Unusual places of thrombosis have been described such as LV thrombus in one case, central retinal vein thrombosis in one case, and two cases of cerebral vein thrombosis [ 7 24 ]. Among reported cases, patient median age was 33.1 years (range 18–53), with the majority of patients in the 4th decade of life (8/19).…”
Section: Discussionmentioning
confidence: 99%